2004
DOI: 10.1097/01.ogx.0000141208.48518.e9
|View full text |Cite
|
Sign up to set email alerts
|

Are Complete Blood Cell Counts Useful in the Evaluation of Asymptomatic Neonates Exposed to Suspected Chorioamnionitis?

Abstract: Radiation exposure of prepubertal, adolescent, and pregnant females may increase the risk of a low-birth-weight (LBW) infant weighing less than 2500 g. It is not clear whether radiation has direct effects on the reproductive organs or influences outcomes indirectly through altering thyroid function. Diagnostic dental radiographs deliver low radiation doses to the hypothalamus-pituitary-thyroid axis but not the reproductive structures or fetus. This population-based case-control study examined the effects of de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
33
1
6

Year Published

2007
2007
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(41 citation statements)
references
References 0 publications
1
33
1
6
Order By: Relevance
“…Overall, 18% of infants with culture-negative sepsis had a normal IT ratio as well as normal CRP at 12 hours of age. In the study by Jackson et al, 13 3 of 4 infants with positive blood culture results had no signs and symptoms of sepsis, and all 4 infants with positive blood culture results had an IT ratio ,0.2 at age 12 hours.…”
Section: Figurementioning
confidence: 99%
See 4 more Smart Citations
“…Overall, 18% of infants with culture-negative sepsis had a normal IT ratio as well as normal CRP at 12 hours of age. In the study by Jackson et al, 13 3 of 4 infants with positive blood culture results had no signs and symptoms of sepsis, and all 4 infants with positive blood culture results had an IT ratio ,0.2 at age 12 hours.…”
Section: Figurementioning
confidence: 99%
“…A massive sample size would be needed to prove that these infants do not require further treatment. Jackson et al 13 reported follow-up data on 98 asymptomatic infants with an abnormal IT ratio at 12 or 24 hours of life. These infants were discharged from the hospital with negative blood culture results after receiving antibiotics for 48 hours.…”
Section: Figurementioning
confidence: 99%
See 3 more Smart Citations